Knowledge, attitudes, beliefs and practises (KABP) of adolescents / young adults (15-24 year of age) attending a private general practice, regarding HIV Voluntary Counselling & Testing (VCT) - Esack, Abdul Aziz (Department of Public Health and Family Medicine, 2018)
Background: By 2005 an estimated 5. 5 million South Africans were living with HIV and the peak prevalence of HIV/AIDS occurs in young people aged 15-24 years. In order to develop prevention strategies aimed at young people, it is important to determine risk behaviours for HIV in this age group. As VCT has been shown to impact on risk behaviours, it is important to determine the accessibility of these services to youth. Aim: This study assessed the knowledge, attitudes, beliefs and practises (KABP) of young adults, 15-24 years of age attending a private general practise, regarding risks for HIV and accessibility of HIV Voluntary Counselling and Testing (VCT) services. Methods: This was a cross-sectional study. A self-administered questionnaire was completed by a sample of 100 patients attending a general practice located in Athlone. Results: Thirty-six of respondents were male and 64 were female. The age range was 15 to 24 years, with a mean age of 20.2 years. The demographic profile of the study population was typical of a formal urban settlement in a traditionally coloured area. Sixty four percent of respondents reported current or previous sexually activity, of which 89% reported that they had one sexual partner over the preceding three months and 58%, reported not using a condom at their last sexual encounter. The mean age of sexual debut was 16 years. Most respondents could identify safer sexual practices. While 97% of respondents had heard of HIV, only 33% knew someone who had died of HIV/AIDS. Most respondents knew how HIV was transmitted and 74% felt that they had never put themselves at risk of contracting HIV. Seventy five percent of respondents had heard of VCT, and 60% had considered having a test. Knowledge regarding the location of VCT testing sites, methods of testing and waiting period for results was generally poor. Most respondents had a favourable impression of staff in the clinic/CHC setting and would return to these facilities for HIV VCT. However, 71 % reported that they were prepared to pay for a HIV test. Respondents reported that having an HIV test would have a positive effect on sexual behaviour; however, only a third would disclose their HIV test result. Discussion: Respondents had high levels of awareness of HIV prevention strategies but these did not always translate into the adoption of appropriate behaviours. This disparity between awareness of HIV prevention strategies and actual risk taking sexual behaviour could reflect inadequacies in current HIV education programmes. Knowledge regarding most aspects of HIV VCT was inadequate, but there was a high willingness to test for HIV. Respondents indicated that they were prepared to pay for VCT. VCT could be used to engage with young adults and impact on behaviour changes. Further studies may be useful to illustrate the potential of VCT as a prevention strategy and to promote the allocation of more resources for this purpose.